IMPLEMENTATION OF THE SABILULUNGAN APPLICATION REPLICATION POLICY IN BANDUNG CITY IN CENTRAL MAMUJU REGENCY - Ni Nyoman Wartati; Daswati; Intam Kurnia (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the implementation of the Sabilulungan Application replication policy, a digital grant management platform from Bandung City to Central Mamuju Regency, using George C. Edwards III's policy implementation model, which includes aspects of communication, resources, disposition, and bureaucratic structure. The research method uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, observations, and documentation studies. Informants were selected through a purposive sampling technique involving the Regional Development Planning Agency (BPKAD), the Communication and Information and Sandi Agency, the Social Welfare Division, and grant implementation staff. Data analysis was carried out through data reduction, presentation, and drawing conclusions using the Miles, Huberman, and Saldaña model. The results show that the implementation of the application replication policy has not been running optimally. The main obstacles lie in the lack of comprehensive policy communication, limited technical human resources, the lack of alignment between regional regulations and application business processes, and a bureaucratic structure that still relies on manual mechanisms. Although the implementer's disposition shows a positive attitude and high commitment, technical and regulatory readiness is not yet adequate to support the digital transition. These findings indicate a design-reality gap between the application design and the actual conditions of the organization. This study confirms that successful digital application replication requires regulatory harmonization, increased human resource capacity, and business process integration as important prerequisites for electronic-based public service transformation.